2013
DOI: 10.1016/j.ceca.2012.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Caspase 3 cleavage of the inositol 1,4,5-trisphosphate receptor does not contribute to apoptotic calcium release

Abstract: An important role in the regulation of apoptotic calcium release is played by the ubiquitously expressed family of inositol 1,4,5-trisphosphate receptor (IP3R) channels. One model for IP3R activation during apoptosis is cleavage by the apoptotic protease caspase 3. Here we show that early elevations in cytosolic calcium during apoptosis do not require caspase 3 activity. We detected a robust increase in calcium levels in response to staurosporine treatment in primary human fibroblasts and HeLa cells in the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…It seems entirely plausible that this could result from steric hindrance by Bok of the ability of chymotrypsin and caspase-3 to access their cleavage sites. This inhibitory effect of Bok may well be biologically relevant, as the C-terminal IP 3 R1 fragment resulting from caspase-3 cleavage has been proposed to form an IP 3 -insensitive, "leaky" channel that contributes toward the apoptotic cascade (40,43), although this notion is controversial (44,50,51). Indeed, a very recent study shows that the IP 3 R1 fragments generated by caspase-3 remain associated and form functional channels fully capable of responding to IP 3 and contributing toward apoptosis (44).…”
Section: Discussionmentioning
confidence: 99%
“…It seems entirely plausible that this could result from steric hindrance by Bok of the ability of chymotrypsin and caspase-3 to access their cleavage sites. This inhibitory effect of Bok may well be biologically relevant, as the C-terminal IP 3 R1 fragment resulting from caspase-3 cleavage has been proposed to form an IP 3 -insensitive, "leaky" channel that contributes toward the apoptotic cascade (40,43), although this notion is controversial (44,50,51). Indeed, a very recent study shows that the IP 3 R1 fragments generated by caspase-3 remain associated and form functional channels fully capable of responding to IP 3 and contributing toward apoptosis (44).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, these latter studies concluded that IP 3 R1 was, if at all, a very late caspase substrate during apoptosis. A recent study has also proposed that caspase activity is not required for the apoptotic Ca 2ϩ increase and that IP 3 -mediated Ca 2ϩ signals, rather than the consequences of IP 3 R1 cleavage, were solely responsible for intracellular Ca 2ϩ elevations associated with staurosporine-induced apoptosis in HeLa cells and human primary fibroblasts (44). An additional scenario was proposed by Khan et al (34) in light of evidence that staurosporine-induced increases in [Ca 2ϩ ] i occurred even in DT40 cells expressing the channel-only domain or fulllength IP 3 R1 with an inactivating channel pore mutation.…”
Section: Discussionmentioning
confidence: 99%
“…4C). Many apoptotic stimuli induce calcium release very early in the apoptotic program (minutes to hours) (44), and this is useful to discern whether the calcium elevations are causative or a consequence of the apoptotic program (45). To measure the effects of simvastatin early in the apoptotic program, we measured cytosolic calcium continuously for the first 5 h after simvastatin administration using the genetically encoded calcium indicator GCaMP6s (37).…”
Section: Simvastatin Induces Changes In Cell Cyclementioning
confidence: 99%